Survival after subsequent non-Hodgkin’s lymphoma and non-small cell lung cancer in patients with malignant thymoma - Parzen, Jacob S.; Bates, James E.; Milano, Michael T.; Dhakal, Sughosh (Journal of Thoracic Disease, 2016)
Background: Survivors of malignant thymoma (MT) are at an increased risk of developing subsequent neoplasms. We compare overall survival (OS) between MT survivors who developed non-Hodgkin’s lymphoma (NHL) or non-small cell lung cancer (NSCLC), and patients with first primary NHL (NHL-1) or NSCLC (NSCLC-1), respectively. Methods: Using the population-based Surveillance, Epidemiology, and End Results (SEER) database for 1973 through 2013, 273,313 patients who had NHL-1, 21 patients with MT-NHL, 566,819 patients with NSCLC-1, and 38 patients with MT-NSCLC were identified. Univariate and multivariate models were used to assess the impact of various factors on OS. Results: The observed-to-expected ratio among MT patients was 2.63 [95% confidence interval (95% CI), 1.40−4.49; P